The importance of salutogenic psychoeducation in mental health disorders – the role of nursing staff - Tkaczyk, Filip M.; Lis, Grażyna T. (Nursing Problems / Problemy Pielęgniarstwa, 2023)
Psychoeducation is the therapeutic pillar of mental disorders. Its task is to increase the awareness of patients and their families about self-control of health and disease. The aim of the study was to demonstrate, based on the latest literature, the role of psychoeducation in mental disorders and the role of nursing staff. Review method was analysis of the literature on psychoeducation and mental health. Data were obtained from a review of electronic databases: PubMed, Google Scholar, and EBSCO. Psychoeducation is one of the methods of treating mental illnesses, especially schizophrenia, depression, and eating disorders. The salutogenic approach used in it affects the development of an individual’s health resources. Undertaking educational activities is a priority in health care. Psychoeducation plays a significant role in the context of the treatment of mental disorders caused by the SARS-CoV-2 virus pandemic.